3x^2+6x=0

Simple and best practice solution for 3x^2+6x=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x^2+6x=0 equation:


Simplifying
3x2 + 6x = 0

Reorder the terms:
6x + 3x2 = 0

Solving
6x + 3x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '3x'.
3x(2 + x) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0

Subproblem 2

Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2

Solution

x = {0, -2}

You can always share this solution

See similar equations:

| x^2-7x=0 | | y^2+6y+8=0 | | 5x^4+31x^2+6=0 | | x^2-10-4x-11=0 | | 5x^3+(2x-12)=1 | | m^2-6m+8=0 | | m^2+10m+9=0 | | m^2+5m+6=0 | | 5x^2+10x+5=180 | | 6(1+8x^3)=9 | | x^3+6x^2=4x+24 | | 5x^2-7x+2=0 | | 2x^2-11x+15=0 | | 4x^2=12x | | 8x^2=72x | | 2x^2-2=-5x-1 | | 0=3x^2-5x-9 | | 3x^2-6x+9=0 | | 3q^2+16=-19q | | (-2x^2+3y^3)+(6x-5)=0 | | 2x^2+6x+4=0 | | 2x^2-5x-75=0 | | 2x^2-10x+18=0 | | 9s^2+3s-20=x | | (x-1)(x^2-4)+2(x-1)(x+2)=(x-1)P | | 9x^2-4.5x-3.5=0 | | 6x^2-5x-14=0 | | x^4-7x-18=0 | | x^2-8x+18=0 | | x^2-8b+18=0 | | 30a^2+am-m^2=0 | | 30a^2+am-m^2=o |

Equations solver categories